SIGNIFICANCE OF THE FALSE CHORDS IN THE LEFT VENTRICLE FOR DIAGNOSTIC APPROACHES IN CHILD CONNECTIVE TISSUE DYSPLASIAS - V. E. Timokhina; K. R. Mekhdieva; A. M. Cherednichenko; F. A. Blyakhman (Кардиоваскулярная терапия и профилактика, 2017)
Aim. The study was aimed on the importance evaluation of the false chords (FC) diagnostics in the left ventricle (LV) of the heart at early age to predict connective tissue dysplasia (CTD) development.Material and methods. The study performed at cardiorheumatological department of MAI “CCCH №11” of Yekaterinburg city. Case histories of 200 patients analyzed, of those had undergone treatment in the department last 6 months. Group consisted of children aged 1 month to 17 year old, mean age 9,7±4,6 y. o. Phenotype of CTD was evaluated according to theGent score criteria (2010) and the Score by Kadurina T. I. et al. Heart structure and functioning were assessed with bi-dimensional transthoracic echocardiography. Statistics was done with SPSS Statistics 17.0 and Microsoft Office Excel 2013.Results. All children had phenotype markers of CTD syndrome. Significance assessment of CTD by Kadurina score was 8,1±3,8 (2-33) points, that is grade 1 severity of CTD. In 17% (n=34) of children there was moderate CTD grade, and in 10% (n=20) there were dysplastic changes in ≥3 organ systems. Most of patients (95,5%) had FC (2,0±0,5 U) localized in various areas of the LV. Chords always correlated with phenotypic CTD markers in other physiological systems. And the number of concomitant markers significantly increased with the children’s age.Conclusion. In most cases CTD syndrome is associated with the changes in the heart, and FC inLV can be regarded as easy approachable and most early and reliable phenotypical marker of this systemic disorder.